2010
DOI: 10.1525/jer.2010.5.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Participant Preferences in Unblinded Randomized Controlled Trials

Abstract: Little research has deliberately investigated the effects of participant preferences for treatment condition in unblinded randomized controlled trials. We designed a study with a non-patient sample comparing a randomized arm to a preference arm of the same trial to investigate: (1) whether having a choice to select one's preference affects feelings about participation, belief in treatment effectiveness, treatment contamination, intervention adherence and engagement, and trial attrition; and (2) the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…The acceptability, usability, and effectiveness of the physical activity intervention was not significantly different for participants matched or mismatched to their preferred intervention delivery mode (video based, text based, or combination). This finding is in line with other studies that have examined preference effects for other types of interventions within different populations [18-20,48]. Only in their study on human papillomavirus testing did McCaffery et al [30] find effects on quality of life based on preferences for different interventions.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The acceptability, usability, and effectiveness of the physical activity intervention was not significantly different for participants matched or mismatched to their preferred intervention delivery mode (video based, text based, or combination). This finding is in line with other studies that have examined preference effects for other types of interventions within different populations [18-20,48]. Only in their study on human papillomavirus testing did McCaffery et al [30] find effects on quality of life based on preferences for different interventions.…”
Section: Discussionsupporting
confidence: 87%
“…Though acceptability of the advice and website usability were not influenced by delivery mode preferences in this study, others have seen an impact of participant satisfaction levels [20]. Therefore, in line with Foley et al [49], we recommend offering participants a delivery mode choice if possible, as it will not harm intervention effectiveness, and might also increase participant satisfaction levels.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The phenomenon has been evidenced by the findings of a systematic review and patient level meta-analysis of 17 musculoskeletal trials, which found patients randomized to their preferred treatment did better than participants who were indifferent to allocation or those who received unopted treatment [14]. However, other studies [8, 15] came to contradictory results and found insufficient empirical evidence in proof of consistent effect of preference on outcomes.…”
Section: Resultsmentioning
confidence: 99%